Facilitating learning in practice : a research-based approach to challenges and solutions - Morley, Dawn A.; Wilson, Kathy (Associate professor); Holbery, Natalie (London : Routledge, 2019)
Many recent high-profile reports have emphasised the need for improvements and innovations in practice-based education for nursing and midwifery students in the UK to ensure safe care delivery. Addressing the new NMC standards of proficiency for pre-registration nursing, this book presents five significant areas of practice learning for student nurses and midwives in their pre-registration education and provides a guiding resource for practitioners at a time of significant change in the ethos and structure of practice learning. Each chapter provides a short case study and helpful learning points to assist readers in the application of the themes to their own practice. This concise and accessible book will act as a key stimulus for reflection on the changes in practice learning environments and will provide invaluable guidance on the new roles of Practice Supervisor, Practice Assessor and Academic Assessor. It will be essential reading for all academics and clinical practitioners who support student nurses and midwives with their practice learning.
OCLC-licensed vendor bibliographic record.
Keywords: Nursing -- Study and teaching (Continuing education); Midwifery -- Education; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; MEDICAL / Clinical Medicine; MEDICAL / Health Care Delivery; MEDICAL / Nursing / Management & Leadership